To the Problem of Law Upbringing of Pupils of 5-6 Forms of Boarding Schools - Olena Polishchuk (Pedagogical Discourse, 2012)
The author of the article studies theoretical aspect of law upbringing of pupils of 5-6 forms of boarding schools. Psychological peculiarities of junior teenagers of general educational boarding schools are elucidated. The specificity of law upbringing of pupils of 5-6 forms of general educational boarding schools is revealed.